Pengabdian Masyarakat Melalui Sosialisasi Anemia Dan Gizi Seimbang Bagi Remaja Putri Di SMK Nusantara Tobelo Kabupaten Halmahera Utara - Jumriani Jumriani; Putri Yayu; Nurbaety (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Efforts need to be made in adolescence to improve the health and nutritional status, especially of adolescent girls, as the next generation and potential development resources. Adolescent girls whose health is maintained will become healthy mothers when entering marriage and pregnancy. Adolescent girls have a 10 times greater risk of experiencing anemia compared to adolescent boys. Unbalanced nutritional status can cause anemia in adolescents. Young women in general are very concerned about their body shape, so they limit their food consumption and are very picky about food. Optimal nutritional status during adolescence is the core of a healthy adolescent life and designs adolescent girls to become good future mothers. Adolescent girls have a 10 times greater risk of experiencing anemia compared to adolescent boys. Unbalanced nutritional status can cause anemia in adolescents. Young women in general are very concerned about their body shape, so they limit their food consumption and are very picky about food. This community service activity will be carried out on Monday 10 June 2024 starting at 10.00-11.30 WIT at SMK Nusantara Tobelo, North Halmahera Regency with material regarding anemia and balanced nutrition in teenagers as well as giving Fe tablets. This activity was attended by 38 young women, 1 teacher, 3 lecturers and most teenagers did not know what anemia and balanced nutrition were.